Analysis of the state of legal regulation of investment activity in Ukraine - Sushch, O. P. (НДІ ПЗІР НАПрН України, 2024)
The research is devoted to the study of the state of legal regulation of investment activity in Ukraine. The author analyzed the current investment legislation and pointed out the existing problems in the legal regulation of investment activity. It is established that the investment legislation of Ukraine needs to be improved according to the current state of investment activity. Наукова робота присвячена дослідженню стану правового регулювання інвестиційної діяльності в Україні. Автор проаналізував чинне інвестиційне законодавство та вказав на існуючі проблеми у правовому регулюванні інвестиційної діяльності. Встановлено, що інвестиційне законодавство України потребує удосконалення відповідно до сучасного стану інвестиційної діяльності.
Keywords: investment; investment activity; legal regulation; social impact; environmental effect; інвестиції; інвестиційна діяльність; правове регулювання; соціальний ефект; екологічний ефект